Pengaruh Current Ratio, Debit To Asset Ratio terhadap Net Profit Margin pada PT Akasha Wira International Tbk Periode 2013-2022 - aulia, hanna Aulia; Lestari, Wiwin Dwi; Amir, Nur Afifah; Kusunadi, Syalsya Frida; Citra Wijaya, Katterina Pangestu (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
This research aims to determine the influence of the Current Ratio and Debt to Asset Ratio on Net Profit Margin at PT/Akasha Wira Internasional in 2013-2022. This research uses quantitative research methods. This population uses secondary data in the form of financial reports from 2013-2022 at PT. Akasha Wira Internasional which is listed on the Indonesian Stock Exchange. The results of the t test (partial) showed that the Current Ratio was not proven to have an effect on the Net Profit Margin, and the Debt to Asset Ratio was not proven to have an effect on the Net Profit Margin. The results of the F test (simultaneous) show that the Current Ratio and Debt to Asset Ratio simultaneously influence the Net Profit Margin.